The application of value management in the Malaysian construction industry and development of prototype value management guidelines / Aini Jaapar - Jaapar, Aini (2006)
This study focuses on value management' (VM) and its application in the construction industry in Malaysia. VM, which is defined as 'a multi-disciplinary, team orientated, structured, analytical process and systematic analysis of function which seeks best value, via the design and construction process to meet the client's perceived needs', is a relatively new field of study in Malaysia. As such, this study investigates the current developments and implementation of VM applications in the construction industry in Malaysia. It then determines whether VM adheres to the procedures and protocols associated with 'value methodology'. This provides the platform for developing a prototype set of VM Guidelines for sustainable and practical application in the Malaysian construction industry. As the knowledge and application of VM in Malaysia is not as sophisticated as in many other countries, an exploratory research design has been deemed appropriate in answering the questions posed. Furthermore, a mixed methodological design that has utilised both quantitative and qualitative approaches has enhanced data collection and analysis. The method of research triangulation adopted in this study has adequately addressed issues related to the methodological rigour of research of this nature and has also addressed issues related to validity and reliability. Documents, literature reviews, surveys, interviews and observations were uniquely juxtaposed in a holistic blend to obtain the data desired in order to map out the landscape of VM field in the Malaysian construction industry. This study has shown that the Malaysian construction industry needs a better approach in project delivery. The data obtained and analysed show that the industry should adopt VM methodology in order to enhance efficiency and to deliver maximum value to its clients. It has also demonstrated the need for the construction industry to be more proactive in its stance and for better and innovative solutions to be integrated into the construction processes. The findings indicated that VM is still in an early stage of development in Malaysia. VM applications were found to occur and adhered to job plan methodology as discovered by Survey 1; confirmed by the observations; detailed by the Survey 2 respondents; elaborated and explained by the interviewees and validated by the VM documents. Its applications also resulted in cost savings, higher client satisfaction and better decision making process. The prototype VM Guidelines that have been developed can improve the future implementation of VM applications in the construction industry in Malaysia. This will not only help to improve the quality of service provided by the industry, but will also be a step towards engendering value-added services of a much higher standard